HUMANIZED PRENATAL CARE: INFLUENCES ON MATERNAL-FETAL OUTCOMES - Antonia Rocha Fiorott, Maria; Martins Eller, Lara; Siqueira Neto, José; Brandão Coelho, Ingrid; Dadalto Scarpati, Elza; Sarlo Pinheiro, Alice; Altoé Pipa Silva, Ivelize; Maia Cruz Brazuna, Ricardo; Cesar Ferreira, Alex; Fernandes Ragonha, Giovanna; Maria Moreno Lobo, Marcelle; Castro Narduci, Jessica; et al. (Health and Society, 2024)
Humanized prenatal care is a concept that aims to ensure that pregnant women receive respectful and personalized care, promoting an emotionally supportive and welcoming environment during pregnancy. This approach aims not only to ensure the physical health of the mother and fetus, but also to improve the psychological and emotional well-being of women during pregnancy, which can have a positive impact on maternal and fetal outcomes. Studies have shown that a humanized approach is a determining factor in reducing complications during pregnancy and childbirth, as well as strengthening the bond between mother and baby. This summary seeks to analyze the influence of humanized care during prenatal care on maternal and fetal outcomes, discussing the importance of welcoming and personalized practices for increasing the quality of care. It also examines how humanized care can have a positive impact on both the physical and emotional health of pregnant women, promoting more favorable outcomes for mother and baby. This study used a qualitative methodology based on a literature review, focusing on humanization practices in prenatal care, exploring their impact on maternal and fetal health and public policy guidelines in Brazil. Humanized prenatal care involves practices such as respect for the autonomy of the pregnant woman, active listening, inclusion of the family in the process and psychological support, as well as comprehensive care for the woman’s physical health. Research shows that pregnant women who receive this type of care have lower rates of anxiety and depression, factors that are associated with obstetric complications and negative outcomes. In addition, humanized care contributes to pregnant women’s adherence to prenatal appointments and tests, reducing the risks of premature births, low birth weight and neonatal mortality. Care that respects a woman’s individuality also facilitates the control of conditions such as hypertension and gestational diabetes, promoting a safer pregnancy. Humanized prenatal care therefore plays a crucial role in maternal and fetal outcomes, promoting a healthier pregnancy and reducing the risks associated with labour and birth. In addition to improving the physical health of the mother and fetus, humanized care strengthens the emotional health of the pregnant woman and facilitates the mother-baby bond, factors that are essential for the healthy development of the newborn. The implementation of humanized practices in health services is therefore a fundamental strategy for improving the quality of prenatal care and promoting better outcomes for mothers and babies.